An obfuscate implementation for Android resources index table - Yang LIU; Weiping WEN (Dianxin kexue)
Android application has risks of reverse, rewrite and repackage. Obfuscate Android resources index table will increase the difficulty of reverse analysis attack. Resources index table records the strings information in Android App. Through analyzing the structure of resources index table, a new obfuscate method was proposed to achieve obfuscate resources index table and increase the difficulty of reverse Android application.